Entrepreneurial Interest Among Physics Education Students in Ethnophysics in the Society 5.0 Era - Dewi Juita; Fatni Mufit; Lufri; Andromeda; Festiyed; Asrizal (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the level of entrepreneurial interest among Physics Education students, with a specific focus on ethnophysics as a potential source of innovation in the Society 5.0 era. Using a quantitative descriptive design, the study involved 75 students from three cohorts (2022–2024) enrolled in a Physics Education program at a public university in Padang, Indonesia. Data were collected through a 20-item Likert-scale questionnaire (1–4) adapted from an established entrepreneurial interest instrument and contextualized for physics and ethnophysics, complemented by brief structured interviews to enrich interpretation. The instrument demonstrated acceptable validity and reliability (Cronbach’s α = .82). Descriptive analysis revealed that students’ entrepreneurial interest was predominantly in the high and moderate categories: 42% (n = 31) were classified as high and 39% (n = 29) as moderate, while 13% (n = 10) and 6% (n = 5) were classified as low and very low, respectively. No students reached the very high category. The mean score was 67.88 (SD = 7.64) on a possible range of 20–80, with a median and mode of 70. These results indicate strong potential for developing ethnophysics-based entrepreneurship initiatives that combine cultural heritage and physics concepts into products with both cultural and economic value. However, reported barriers—including limited confidence, fear of failure, and insufficient institutional support—suggest the need for curricular strengthening, skills training, and the development of an entrepreneurship ecosystem within the university. The findings contribute empirical evidence to inform the design of adaptive entrepreneurship education in physics teacher preparation programs.